Vector control strategy for motor‐generator pair drive inverters in parallel operation. Issue 11 (16th April 2021) - Li, Chenyang; Huang, Yongzhang; Guan, Fei; Fu, Wenqi; Wu, Qianyu
Abstract: In view of the weak moment of inertia for power system with high penetration of renewable energy and limited transient voltage support of power electronics, a synchronous motor‐generator pair (MGP) is proposed as a possible solution for renewable energy integration to improve grid stability. In order to realize the large‐scale renewable energy integration, parallel inverters drive MGP is an ideal control scheme. Firstly, the working principle and mathematical model of MGP are introduced. Then based on a comparative analysis of control of parallel inverters and torque control of synchronous motors, the decoupling vector control method of MGP is proposed. Considering the linear relation between q ‐axis current and the active power in the rotor flux‐oriented mode, the strategy of parallel drive for MGP with vector control is established. Different control loop for off‐grid and grid‐connected operation is designed, and effectiveness of this control strategy is verified by simulation. Finally, a 5 kW MGP experimental platform with dual inverters is built, the parameters are selected to test stability of the system, and power distribution and efficiency are studied. The results indicate that the parallel operation of MGP is stable under dynamic conditions, the strategy can realize the independent control of each inverter.